2018
DOI: 10.1158/2159-8290.cd-17-0912
|View full text |Cite
|
Sign up to set email alerts
|

CDK6 Antagonizes p53-Induced Responses during Tumorigenesis

Abstract: Tumor formation is a multistep process during which cells acquire genetic and epigenetic changes until they reach a fully transformed state. We show that CDK6 contributes to tumor formation by regulating transcriptional responses in a stage-specific manner. In early stages, the CDK6 kinase induces a complex transcriptional program to block p53 in hematopoietic cells. Cells lacking CDK6 kinase function are required to mutate (encoding p53) to achieve a fully transformed immortalized state. CDK6 binds to the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 54 publications
5
75
0
Order By: Relevance
“…The results indicated that the expression of oncoprotein TRIM59 positively correlates with Cyclin CDK6 expression in Wang cell line 2 (A549 cells) and Lee Lung (lung adenocarcinoma and squamous cell lung carcinoma tissue) (Figure A,B). As up‐regulation of CDK6 is closely associated with growth and metastasis of different cancers . This prompted us to test whether TRIM59 promoted cancer growth and metastasis by regulating CDK6 expression through ERK signalling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the expression of oncoprotein TRIM59 positively correlates with Cyclin CDK6 expression in Wang cell line 2 (A549 cells) and Lee Lung (lung adenocarcinoma and squamous cell lung carcinoma tissue) (Figure A,B). As up‐regulation of CDK6 is closely associated with growth and metastasis of different cancers . This prompted us to test whether TRIM59 promoted cancer growth and metastasis by regulating CDK6 expression through ERK signalling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…As up-regulation of CDK6 is closely associated with growth and metastasis of different cancers. 11,[16][17][18] This prompted us to test whether TRIM59 promoted cancer growth and metastasis by regulating CDK6 expression through ERK signalling pathway. This speculation is verified by the observations that CDK6 mRNA and protein expression significantly decreased when TRIM59 is down-regulated by transducing lung cells with TRIM59 shRNA ( Figure 5A).…”
Section: Trim59 Induced Up-regulation Of Cdk6 Expression Is Dependementioning
confidence: 99%
“…Moreover, it was shown that malignant transformation of hematopoietic cells depend on CDK6-mediated repression of p53 activity, and that CDK6 inhibition could reverse this effect 33 . However, the genomic landscape of cancer cells remains highly heterogeneous and unstable, making the demonstration of a direct correlation between p53 activity and irreversible cell cycle arrest in tumors a challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some MCPH gene overexpression promotes cancer cell progression, sometimes through the regulation of p53 activity. MCPH12 contributes to tumor formation by inducing a complex transcriptional program to block p53 in hematopoietic cells [132]. Microarray and bioinformatics analyses indicate that the overexpression of the MCPH17 gene in human colon cancer tissue can affect the occurrence of cancer through the p53 signaling pathway [26].…”
Section: Gene Neurogenesis Ref Carcinogenesismentioning
confidence: 99%